PENGARUH SIZEPERUSAHAAN, KEPUTUSAN PENDANAAN, PROFITABILITAS DAN KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN - Entis Haryadi (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2016)
Creation of a company's value can have a positive impact to stakeholders including shareholders ,. This study aimed to test empirically about the influence of Company Size, funding decisions, profitability and investment decisions on firm value. This research was carried out on non-financial companies listed on the Indonesia Stock Exchange (IDX) which publishes the financial statements for the period of 2013. By using purposive sampling technique and the company obtained 263 samples analyzed using multiple linear regression.These results indicate that the size / size company in proksikan with Debt to Equity Ratio (DER) has no effect on the value of the company, while profitability in proksikan with Return On Equity (ROE) and investment decisions are proxied by the Market to Book Value of Equity (MBVE) effect on firm value. From the results of multiple regression analysis known that simultaneously, Size / size of the company, funding decisions, profitability and investment decisions jointly affect the value of the company. Adjusted R² value of 0.174, this shows that the variation in the value of the company can be explained by Size companies, funding decisions, profitability and investment decisions by 17.4% and the remaining 82.6% is influenced by factors - other factors outside the model.  Keywords: Size of the company, funding decisions, profitability and investment decisions.